Direct Evidence of Powassan Virus Vertical Transmission in Ixodes scapularis in Nature - Rachel E. Lange; Melissa A. Prusinski; Alan P. Dupuis; Alexander T. Ciota (Viruses, 2024)
Powassan virus (POWV) is a tick-borne flavivirus endemic in North America and Russia. Experimental infections with POWV have confirmed horizontal, transstadial, vertical, and cofeeding transmission routes for potential virus maintenance. In the field, vertical transmission has never been observed. During New York State tick-borne pathogen surveillance, POWV RNA and/or infectious POWV was detected in five pools of questing Ixodes scapularis larvae. Additionally, engorged female I. scapularis adults were collected from hunter-harvested white-tailed deer (Odocoileus virginianus) in a region with relatively high tick infection rates of POWV and allowed to oviposit under laboratory conditions. POWV RNA was detected in three female adult husks and one pool of larvae from a positive female. Infectious virus was isolated from all three RNA-positive females and the single positive larval pool. The detection of RNA and infectious virus in unfed questing larvae from the field and larvae from replete females collected from the primary tick host implicates vertical transmission as a potential mechanism for the maintenance of POWV in I. scapularis in nature, and elucidates the potential epidemiological significance of larval ticks in the transmission of POWV to humans.